2019
DOI: 10.1021/acsami.9b08015
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Carbon Dioxide Adsorption Affinity of Zinc(II) MOFs by Mixing Bis(pyrazolate) Ligands with N-Containing Tags

Abstract: The four zinc(II) mixed-ligand MOFs (MIXMOFs) Zn(BPZ)x(BPZNO2)1-x, Zn(BPZ)x(BPZNH2)1-x, Zn(BPZNO2)x(BPZNH2)1-x and Zn(BPZ)x(BPZNO2)y(BPZNH2)1-x-y (H2BPZ = 4,4'-bipyrazole; H2BPZNO2 = 3-nitro-4,4'-bipyrazole; H2BPZNH2 = 3-amino-4,4'-bipyrazole) were prepared through solvothermal routes and fully investigated in the solid state. Isoreticular to the endmembers Zn(BPZ) and Zn(BPZX) (X = NO2, NH2), they are the first examples ever reported of (pyr)azolate MIXMOFs. Their crystal structure is characterized by a 3-D o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 71 publications
3
30
0
Order By: Relevance
“…As shown in Figure 3 a, both compounds show a type IV isotherm, typical of micro‐mesoporous materials. As expected, they are featured by comparable BET areas [463 and 504 m 2 g −1 for Zn(3,3′‐L) and Zn(3,5‐L) , respectively] that fall in the same range as those measured for Zn(BPZNH 2 ) (395 m 2 g −1 ) [4c] and for the MIXMOF Zn 2 (BPZ)(BPZNH 2 ) (502 m 2 g −1 ) [4b] . The t ‐plot analysis revealed that the main contribution to the total surface area comes from micropores for both MOFs [77 and 57 % for Zn(3,3′‐L) and Zn(3,5‐L) , respectively].…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…As shown in Figure 3 a, both compounds show a type IV isotherm, typical of micro‐mesoporous materials. As expected, they are featured by comparable BET areas [463 and 504 m 2 g −1 for Zn(3,3′‐L) and Zn(3,5‐L) , respectively] that fall in the same range as those measured for Zn(BPZNH 2 ) (395 m 2 g −1 ) [4c] and for the MIXMOF Zn 2 (BPZ)(BPZNH 2 ) (502 m 2 g −1 ) [4b] . The t ‐plot analysis revealed that the main contribution to the total surface area comes from micropores for both MOFs [77 and 57 % for Zn(3,3′‐L) and Zn(3,5‐L) , respectively].…”
Section: Resultssupporting
confidence: 75%
“…The isosteric heat of adsorption reflects the interaction strength between CO 2 and the inner pore walls of the two MOFs. Mirroring the trend observed for the CO 2 storage capacity, the values of 24.8 and 25.4 kJ mol −1 calculated at zero coverage for Zn(3,3′‐L) and Zn(3,5‐L) , respectively, are higher than that of their untagged isostructural analogue [Zn(BPZ); Q st = 23.7 kJ mol −1 ] [4b, 21] but much lower than those calculated for Zn(BPZNH 2 ) ( Q st = 35.6 kJ mol −1 ), [4c] Zn 2 (BPZ)(BPZNH 2 ) ( Q st = 30.8 kJ mol −1 ) [4b] and Zn(BDPNH 2 ) ( Q st = 28.1 kJ mol −1 ) [4d] . This is a further proof of evidence that the tag “dilution” in the solid matrix is of fundamental importance to minimize the intermolecular interactions between adjacent dangling tags in the lattice and consequently to improve the material thermodynamic response towards external guest gases.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…[10] Recently,m ultivariate MOFs (MTV-MOFs)c onstructed by virtue of multiple linkersw ith different functional groups have exhibited interesting properties such as enhanced gas adsorption capacity. [11] In MTV-MOFs, the coordination environmento f the metal centers can be precisely regulated by ligands, which will further change the electron distribution of the metal centers. Therefore, the multivariate MOFs approach introducing different ligands can meet the requirements of tuning the SCO properties.…”
Section: Introductionmentioning
confidence: 99%